Sickness recovery intensities for short term health insurance in Greece - George Mavridoglou; Peter Kiochos (SPOUDAI - Journal of Economics and Business, 2011)
The last decennium a vast literature on multiple state models and stochastic models for disability (health) insurance has been developed. In our paper, with title sickness recovery intensities for short term health insurance in Greece, examines two methodologies for graduating sickness recovery intensities in a multistate model for short term health insurance. The approach is based on generalized linear models and utilizes the data collected for a Greek Social Security Institution. The sickness recovery intensity is function of age at sickness onset, x, and duration of sickness, z. The graduation formula that proposed for Greek experience has three break-point predictors
Keywords: C49; G22; I12; 330; Disability Insurance; average duration of a claim; sickness recovery intensities; graduation process